Educational Technologies in Support of Pedagogical Activity and Public Health Improvement Amidst the Implementation of State Policies on Humanistic-Legal Values in Education - Mykoliuk , Andriy; Budzyn, Vira; Rybchych , Ivan; Bazyliak, Nataliia; Yaroshovych, Volodymyr; Kharechko, Dmytro (Journal of Ecohumanism, 2024)
The integration of educational information technologies into pedagogical practices and public health initiatives embodies a sophisticated, transformative approach within modern education. This integration aligns with state policies that champion humanistic and legal values. Such technologies revolutionize the delivery of educational content, enhancing engagement, inclusivity, and effectiveness. This article aims to explore how these technologies aid in maintaining and nurturing the psychological health of educational institution students. The research employs contemporary modeling methods to understand the upkeep and support of students' psychological health. Today, the significance of health for both individuals and society is accentuated by factors like environmental conditions, socioeconomic status, and lifestyle. Preventive efforts are increasingly focused not just on specific ailments but on broader health promotion. The study of health, especially within the humanities and social psychology, is gaining prominence. These fields examine the mechanisms that encourage healthy lifestyles and preventive behaviors. The article presents a primary model for preserving and nurturing psychological health among students, highlighting the pivotal role of educational technologies in this context.